ASCORBIC ACID TURNOVER IN THE OCULAR TISSUES OF SOME FISHES
The ascorbic acid turnover from the ocular tissues of 11 species of fishes from a culture pond and the river Godavari has been studied. The free ascorbic acid and ascorbigen contents were more in the case of bottom or deep dwelling fishes and the least in the case of surface living forms, depending upon the light. nenetration in the area that each species inhabits. The enzymic utilization and ascorbic acid-macromolecule complex varied among the fishes possibly de